On characterization of B-canal surfaces in terms of biharmonic B-slant helices according to Bishop frame in Heisenberg group Heis3 - Korpinar, Talat; Turhan, Essin (Academic Press Inc Elsevier Science, 2011)
In this paper, we study B-canal surfaces in terms of biharmonic B-slant helices according to Bishop frame in the Heisenberg group Heis(3). We give necessary and sufficient conditions for B-slant helices to be biharmonic. We characterize B-canal surfaces in the Heisenberg (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Biharmonic curve; Bishop frame; Heisenberg group; Canal surface